Parallelizable PARAFAC decomposition of 3-way tensors - Nguyen, Linh-Trung; Abed-Meraim, Karim; Nguyen, Linh-Trung (2015 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2015)
This paper introduces a new PARAFAC algorithm for a class of third-order tensors. Particularly, the proposed algorithm is based on subspace estimation and solving a non-symmetrical joint diagonalization problem. To deal with large scale problem, a procedure for overcoming scale and permutation ambiguities is proposed in a parallel computing scheme leading to a significant cost reduction of our method. Performance comparison with some state-of-the-art algorithms produces promising results.